High content analysis provides mechanistic insights on the pathways of toxicity induced by amine-modified polystyrene nanoparticles. - Sergio Anguissola (PLoS ONE, 2014)
The fast-paced development of nanotechnology needs the support of effective safety testing. We have developed a screening platform measuring simultaneously several cellular parameters for exposure to various concentrations of nanoparticles (NPs). Cell lines representative of different organ cell types, including lung, endothelium, liver, kidney, macrophages, glia, and neuronal cells were exposed to 50 nm amine-modified polystyrene (PS-NH2) NPs previously reported to induce apoptosis and to 50 nm sulphonated and carboxyl-modified polystyrene NPs that were reported to be silent. All cell lines apart from Raw 264.7 executed apoptosis in response to PS-NH2 NPs, showing specific sequences of EC50 thresholds; lysosomal acidification was the most sensitive parameter. Loss of mitochondrial membrane potential and plasma membrane integrity measured by High Content Analysis resulted comparably sensitive to the equivalent OECD-recommended assays, allowing increased output. Analysis of the acidic compartments revealed good cerrelation between size/fluorescence intensity and dose of PS-NH2 NPs applied; moreover steatosis and phospholipidosis were observed, consistent with the lysosomal alterations revealed by Lysotracker green; similar responses were observed when comparing astrocytoma cells with primary astrocytes. We have established a platform providing mechanistic insights on the response to exposure to nanoparticles. Such platform holds great potential for in vitro screening of nanomaterials in highthroughput format.